142k views
1 vote
Evaluate the expression below

Evaluate the expression below-example-1
User Domos
by
6.6k points

1 Answer

1 vote

Answer: b. 195,312

Explanation:


\sum\limits_(i=1)^8-3*(-5)^(i-1).\\

Let's solve using a geometric progression:


b_1=-3\ \ \ \ q=-5\ \ \ \ S_8=?\\

The formula for the sum of a geometric progression


\displaystyle\\\boxed {S_n=b_1*(q^n-1)/(q-1) }


\dIsplaystyle\\\\S_8=-3*((-5)^8-1)/(-5-1)\\\\S_8=(-3*390625)/(-6)\\\\S_8=(390625-1)/(2)\\ \\S_8=(390624)/(2)\\\\S_8=195312.

User Abdull
by
5.9k points